Reaction of some substituted isatin with per-o-acetyl--d-glucopyranosyl thiosemicarbazide - Thanh, Nguyen Dinh; Kim Giang, Nguyen Thi; Quyen, Tran Ha (Vietnam Journal of Chemistry, 2012)
Seven new substituted isatin (2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)thiosemicarbazones were synthesized by reaction of 2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl thiosemicarbazide and corresponding substituted isatin using microwave-assisted heating method.